Use of plasma ctDNA as a potential biomarker for longitudinal monitoring of a patient with metastatic high-risk upper tract urothelial carcinoma receiving pembrolizumab and personalized neoepitope-derived multipeptide vaccinations: a case report. Issue 1 (11th January 2021) - Blumendeller, Carolin; Boehme, Julius; Frick, Maximilian; Schulze, Martin; Rinckleb, Antje; Kyzirakos, Christina; Kayser, Simone; Kopp, Maria; Kelkenberg, Sabine; Pieper, Natalia; Bartsch, Oliver; Hadaschick, Dirk; et al.
Abstract : Upper tract urothelial carcinoma (UTUC) is often diagnosed late and exhibits poor prognosis. Only limited data are available concerning therapeutic regimes and potential biomarkers for disease monitoring. Standard therapies often provide only insufficient treatment options. Hence, immunotherapies and complementary approaches, such as personalized neoepitope-derived multipeptide vaccine (PNMV), come into focus. In this context, genetic analysis of tumor tissue by whole exome sequencing represents an essential diagnostic step in order to calculate tumor mutational burden (TMB) and to reveal tumor-specific neoantigens. Furthermore, disease progression is essential to be monitored. Longitudinal screening of individually known mutations in plasma circulating tumor DNA (ctDNA) by the use of next-generation sequencing and digital droplet PCR (ddPCR) might be a promising method to fill this gap. Here, we present the case of a 55-year-old man who was diagnosed with high-risk metastatic UTUC in 2015. After initial surgery and palliative chemotherapy, he developed recurrence of the tumor. Genetic analysis revealed a high TMB of 41.2 mutations per megabase suggesting a potential success of immunotherapy. Therefore, in 2016, off-label treatment with the checkpoint-inhibitor pembrolizumab was started leading to strong regression of the disease. This therapy was then discontinued due to side effects and treatment with a previously produced PNMV was started that induced strong T cell responses. During both treatments, plasma Liquid Biopsies (pLBs) were performed to measure the number of mutated molecules per mL plasma (MM/mL) of a known tumor-specific variant in the MLH1 gene by ddPCR for longitudinal monitoring. Under treatment, MM/mL was constantly zero. A few months after all therapies had been discontinued, an increase of MM/mL was detected that persisted in the following pLBs. When MRI scans proved tumor recurrence, treatment with pembrolizumab was started again leading to a rapid decrease of MM/mL in the pLB to again zero. Treatment response was then also confirmed by MRI. This case shows that use of immunotherapy and PNMV might be a promising treatment option for patients with high-risk metastatic UTUC. Furthermore, measurement of individually known tumor mutations in plasma ctDNA by the use of pLB could be a very sensitive biomarker to longitudinally monitor disease.